2021
DOI: 10.1016/j.aninu.2021.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with inulin improves lactation performance and serum lipids by regulating the rumen microbiome and metabolome in dairy cows

Abstract: This study investigated the effects of inulin on rumen fermentation parameters, ruminal microbiome and metabolites, as well as lactation performance and serum indexes in dairy cows. Sixteen Holstein dairy cows with similar body conditions were randomly divided into 2 groups ( n = 8 per group), with inulin addition at 0 and 200 g/d per cow. The experiment lasted for 6 weeks, including a 1-week adaptation period and a 5-week treatment period. At the end of the experimental period, the milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 58 publications
1
29
0
2
Order By: Relevance
“…Previous studies have suggested that extracts from natural plants could affect the composition of rumen microorganisms in ruminants ( Jiao et al, 2021 ; Wang et al, 2021 ). Bacteroidetes and Firmicutes are the predominant phyla in the ruminal microbial community, which is consistent with our results ( Scharen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that extracts from natural plants could affect the composition of rumen microorganisms in ruminants ( Jiao et al, 2021 ; Wang et al, 2021 ). Bacteroidetes and Firmicutes are the predominant phyla in the ruminal microbial community, which is consistent with our results ( Scharen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by increasing the molar proportion of acetate, the ratio of acetate to propionate and by increasing the molar proportion of propionate in the rumen fluid of Holstein cows. Wang et al (2021a) reported a significant increase in the milk production of Holstein cows through the addition of inulin, which is due, among other factors, to an increase in the production and concentration of rumen propionate. Short-chain fatty acids (6-14 carbon fatty acids) in milk are formed mainly by de novo synthesis from acetate and butyrate produced in mammary gland epithelial cells in the rumen, and 16 carbon fatty acids in milk are both produced by de novo synthesis and fatty acids absorbed from the blood (Liu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Milk lipid composition was further analyzed according to the acetyl chloride-methanol methyl esterification method presented by Wang et al ( 19 ). Parameters including saturated fatty acid (SFA), monounsaturated fatty acid (MUFA), and polyunsaturated fatty acid (PUFA) were measured.…”
Section: Methodsmentioning
confidence: 99%